Abordagem sistemática para elaboração da especificação de produtos eletrodomésticos - Morosini, Marcel Monteiro (2013)
In order for a new product development to have better chances of success in today’s competitive market, companies should focus on meeting the real consumer needs in their projects. Thus, it is necessary that the consumer wishes be transformed correctly into clear and objective product specifications. Otherwise, the incorrect or subjective target specifications could generate a product which does not fulfill to the consumer expectations. It is known that the redesign and rework needed due to product modifications would involve loss of time, cost and quality. So, the specification elaboration process during the product development is critical to achieve the targets as time-to-market, cost and quality of the final product. The translation of the voice of customer into project technical requirements is usually accomplished by such methods as, for example, QFD. However, the QFD is not used very often in several industries, like the home appliances factory, because it is general and difficult to use. Therefore, the main objective is to develop a systematic approach for a home appliance specification elaboration, in this case, a cooker. A field study was conducted in a company of this branch to verify the research opportunity and data collection for the method and tool development. Next, an electronic spreadsheet toll was developed for automatically generate the target specifications of a cooker from input data of the project. The systematic validation was implemented by the comparative analysis among the results obtained by the tool with previous products already developed by the researched company. The result of this study indicates that the method proposed is a mechanism for generating specifications in a simple and practical way, contributing to greater assertiveness in product development and can be embedded in the daily-basis process of the company.